Un-structuring Museums: reclaiming agency and space in the Company Gardens - Phiri, Sarah (School of Architecture, Planning and Geomatics, 2023)
This dissertation explores the impact of colonial museum-making methods on the communities which they serve and the human body. Based on this research it then proposes alternative approaches to museum-making in a post-colonial context. The inquiry begins with an exploration of the history of museums in within a European, and then a South African context. It then goes on to look at the physical effects museums have on the human body and how people choose to engage as a result. This entry point ends with a summary of what people may need to be physically able to better engage with museums. The dissertation then goes to identify the Company Gardens as a site area and looks to its narrative as a guide to design. Based on this process, emerges an architectural intervention of an indigenous botany library and museum that aims to share the narrative of indigenous plants and Khoisan-based plant knowledge through its design. Initially, this dissertation aimed to find a fixed framework and approach to de-colonial museum design. But through the research process it becomes clear that there is no fixed approach to de- colonial museum design but rather it is a context-based process. This project becomes about reclaiming a previously colonised space and regaining agency of narrative. It attempts to disrupt colonial continuities that are still present in the Company Gardens.